Feasibility of North Tangerang Toll Road Construction - Yafril Yafril; Bambang Priyambodho (Syntax Corporation Indonesia, 2023)
In order for an investment to be efficient, an economic and financial feasibility study is needed so that all parties involved, the government, banks as lenders and investors (Toll Road Business Entities) understand the risks that will occur. An economic study is needed to know the magnitude of the benefits of this project for the surrounding community, while a financial study is needed to find out whether this project is feasible to build in economic or finance. This thesis will examine the economic and financial feasibility analysis of this toll road project, from existing secondary data, the feasibility study is calculated using the criteria of IRR (Internal Rate of Return), NPV (Net Present Value), B/C ratio and PP (Payback Period). Feasibility calculation will be greatly influenced by several variables, for sensitivity and risk analysis on investment feasibility the variables that are taken into account are initial construction costs, traffic volume and loan interest. From the results of the economic feasibility analysis, it was obtained that EIRR = 17.87% > 6.75 % ID Govt. Yield 10 yr-2021, NPV (MARR 6.75%) = Rp.27,874,162 (million) and B/C ratio = 5.46 > 1, while financial feasibility is obtained FIRR = 13.63% > MARR 10%, NPV = Rp. 3,594,555. (millions), B/C ratio = 1.58 > 1, Payback Period = 7.92 and Total operational loans = Rp. 5,298,231 (million) for 11 years. The variables that greatly influence the IRR are the variable initial construction costs of -72.3%, then traffic volume of 48.5% and loan interest -15.5%. Based on the results of the study and analysis, it can be said that the North Tangerang toll road project is economically feasible and financially feasible, however, in its implementation, it is necessary to control the cost and time plans as well as the quality of implementation, so that the feasibility calculation will not change much from what has been planned.